Using action research and organization development strategies for change in a hierarchical organization : duct tape, band-aids, and post-it notes - Anderson, David W. (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"As academics, Organization Development (OD) change professionals, and leaders, many of us have faced the challenge of driving change within a traditionally resistant organization. This book is focused on blending theory and practice to explore a transformational change process in an environment many might not immediately consider: a mid-sized police department in the Midwest. Although it is not your typical business setting, the lessons learned are universally applicable to many public sector and traditionally hierarchical organizations. Many organizations have deeply ingrained cultures that create barriers to bridging the gap between theory and practical application. Insider action research (IAR) can be a bridge that allows for not only the generation of intentional change in the organization but also the creation of theoretical knowledge through engaging organizational members in researching and changing their organization. Through IAR and the implementation of multiple OD strategies, over the course of this 3 year study, the research team engaged in rich qualitative data gathering through interviews, unstructured interactions, meetings, and the review of organizational documents and historical performance. This data was combined through an iterative descriptive coding process resulting in the identification of six opportunities for change in the department. These opportunities for change were used to generate seven core IAR projects and 11 self-organization process improvement action research projects. Organizational culture was measured longitudinally using Cooke and Lafferty's (1983) Organizational Culture Inventory were taken and demonstrated a positive culture change in the organization. IAR was combined with Use of Self (UoS), open systems diagnosis, dialogical systems perspective generation, survey feedback, and Appreciative Inquiry (AI) to generate both micro-changes or small intentional changes and transformational changes in a historically difficult police environment"-- Provided by publisher.
Keywords: Organizational change.; Corporate culture.; Management.; Business & Economics -- Organizational Development.; Organizational theory and behaviour.; elektronické knihy; electronic books